Study on the Effect of Surface Micro-texture on the Friction and Wear Performance of Brass - Chen, Junfeng; Deng, Xiaofan (International Journal of Mechanical and Electrical Engineering, 2025)
Brass is widely used in the manufacturing of various components due to its excellent mechanical properties, corrosion resistance, and good machinability. However, with increasingly complex working environments, the friction and wear performance of brass components has become insufficient to meet practical demands. In this study, precision ultraviolet laser machining technology was employed to fabricate four types of micro-textures—scale, rhombus, ellipse, and line—on the surface of H59 brass. The effects of micro-texture shape, diameter, depth, and area density on the friction and wear properties of brass under dry and abrasive wet friction conditions were systematically investigated. The results showed that elliptical micro-textures with a major axis of 200 μm, a minor axis of 100 μm, a depth of 125 μm, and an area density of 10% reduced the friction coefficient from 0.22 to 0.12 under dry friction conditions, with a wear rate reduction of 17.3%. Under abrasive wet friction conditions, the friction coefficient decreased from 0.52 to 0.23, with a wear rate reduction of 28.9%. The results demonstrate that elliptical micro-textures significantly enhance the wear resistance of brass components.